EFEKTIVITAS GURU PAI DALAM MENERAPKAN PRAKTIK BERWUDHU PADA ANAK BERKEBUTUHAN KHUSUS (ABK) DI SLB PEMBINA BENER MERIAH - Murniati, Murniati (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2024)
Islamic Religious Education is a conscious and planned effort in teaching and learning activities to prepare students to develop potential through guiding, training and directing activities and practicing as an effort to achieve the unity of the National Education Curriculum, especially for children with special needs. therefore, in this study want to examine (1) how the planning of PAI teachers in learning Islamic Religious Education in Learning Ablution Practices of children with special needs at SLB Negeri Pembina Bener Meriah; (2) Teaching methods of PAI teachers in Learning Ablution Practices of children with special needs at SLB Negeri Pembina Bener Meriah. This research uses case study research with a qualitative approach. Data collection techniques through observation, interviews and documentation. The results of the research obtained: (1) planning done by PAI teachers in learning ablution practices in children with special needs in SLB Negeri Pembina Bener Meriah is referring to the curriculum and vision and mission of national education by preparing lesson plans and learning methods that are in accordance with the characteristics of the needs of children with special needs; (2) The methods used in learning ablution practices in children with special needs in SLB Negeri Pembina Bener Meriah are for children with Down syndrome using one task behavior method, children with tunagrahita and tunadaksa using lecture and demonstration methods